2006
DOI: 10.1182/blood-2006-07-035006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and safety of intravenous pegaspargase during remission induction in adults aged 55 years or younger with newly diagnosed acute lymphoblastic leukemia

Abstract: In contrast to that in children, pharmacokinetic, pharmacodynamic, and safety information on pegaspargase in adults is very limited. We administered a single intravenous dose of pegaspargase (2000 IU/m 2 ) as part of a standard frontline induction regimen to 25 adults with newly diagnosed acute lymphoblastic leukemia (ALL), and obtained serum samples on several time points. The population mean peak serum concentration of asparaginase enzymatic activity was 1 IU/mL, the elimination half-life was 7 days, and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 45 publications
1
106
1
4
Order By: Relevance
“…[21] Another modeling study in adult ALL patients found that PEG-asparaginase activity levels of 0.2 IU/mL were required to achieve 90% asparagine depletion. [101] Since suboptimal depletion has been associated with poor outcomes, caution should be exercised in continuing patients on a treatment that does not sufficiently deplete their asparagine. If subclinical hypersensitivity is identified, it is recommended that patients be switched to the alternate formulation asparaginase Erwinia chrysanthemi.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…[21] Another modeling study in adult ALL patients found that PEG-asparaginase activity levels of 0.2 IU/mL were required to achieve 90% asparagine depletion. [101] Since suboptimal depletion has been associated with poor outcomes, caution should be exercised in continuing patients on a treatment that does not sufficiently deplete their asparagine. If subclinical hypersensitivity is identified, it is recommended that patients be switched to the alternate formulation asparaginase Erwinia chrysanthemi.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Thus, it is easily inferred that patients with ALL with the triple repeat allele (3R) of the ASNS gene may have improved event-free survival and outcomes, whereas patients with haplotype à 1 may have lower PD activity by ASNase (9)(10)(11)(12). The clinical PD relationships between ASNase and ASNS, even though well understood, were not fully elucidated until the recent articles on the polymorphisms of ASNS.…”
Section: Clinical Data On Asn Deamination and Asnsmentioning
confidence: 99%
“…It has been reported that the incidence of allergic reaction is as high as 30% after l ‐asparaginase treatment 31. Studies have found that pegaspargase has similar efficacy as l ‐asparaginase in treating acute lymphoblastic leukemia in children32, 33, 34, 35 and has about a 5 times longer half‐life with therapeutic effects being maintained for about 2 weeks 23, 36, 37. Polyethylene glycol‐asparaginase also requires lower and less frequent dosing 36.…”
Section: Introductionmentioning
confidence: 99%